Subclinical hyperthyroidism - Mohammad Reza Kalantar Hormozi (Iranian South Medical Journal, 2013)
Background: Subclinical hyperthyroidism occurs when peripheral thyroid hormone levels are within the normal labaratory reference range and serum thyroid stimulating hormone level is less than normal. For patients with sustained subclinical hyperthyroidism (serum TSH level< 0/1mlu/L), therapy is recommended especially in older patients. Observation or selective therapy should be considered for patients with: Serum TSH level between 0/1 and 0/4 mlu/L and postmonoposel osteoprosis, recent atrial fibrillation congestive heart failure, angina pectoris and infertility or menstrual disorder. This review article aimed to assess the indication of treatment of the patients with subclinical hypothyroidism. Material and Methods: The sample size of this study was the article index in block cochrance, embase, pubmed databases and enutained the terms subclinical hyperthyroid, thyroxin, and thyrotropin. Results: 209 articles were found that 53 articles were investigated for this issue. The results are discussed under the subtitles such as subclinical hypothyroidism and indication of treatment of subclinical hyperthyroidism. Conclusion: In this summary, we tried to review the current literature about subclinical hyperthyroidism and indication of treatment of subclinical hyperthyroidism.